DIMENSI MORAL DAN SPIRITUAL DALAM KONSEP AL-KASB: FONDASI ETIS EKONOMI ISLAM KONTEMPORER (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to explore the moral and spiritual dimensions of the concept of al-Kasb, as well as its relevance as an ethical foundation in contemporary Islamic economics. This study uses a qualitative approach with a library research design. The data used include classical works, such as the book al-Kasb by al-Syaibani and al-Ghazali, as well as contemporary literature on Islamic economics. The analysis was conducted using thematic content analysis to identify and categorize the moral and spiritual concepts contained in al-Kasb and their relevance to contemporary Islamic economic practices. The results show that al-Kasb contains moral dimensions that include honesty, trustworthiness, justice, and social responsibility, as well as spiritual dimensions that involve the intention of worship, monotheism, and an orientation towards the afterlife. This concept provides an ethical foundation that aligns with the principles of maqasid al-Shari'ah and can serve as a basis for building a just, inclusive, and sustainable economy. In the context of contemporary Islamic economics, al-kasb can correct the materialistic tendencies of capitalism by emphasizing the balance between material and spiritual goals, and encouraging economic practices that are fairer and more beneficial to all levels of society.